92 Physician Training and Experience (Hair Transplantation, 2023)
The field of hair restoration surgery has evolved over the years, and the training of a hair restoration surgeon has evolved as well. Both the International Society of Hair Restoration Surgeons (ISHRS) and the American Board of Hair Restoration Surgery (ABHRS) have developed standards and goals for training programs in hair restoration surgery to ensure that the education gained is the most comprehensive. A fellowship program can vary from 1 to 2 years, following the core competencies and the curriculum guidelines of the ISHRS. Case logs and evaluations are performed to ensure that the above are achieved and that the fellow is a competent and confident hair restoration surgeon. Following a fellowship, the hair restoration surgeon will be able to attend meetings held by the ISHRS, and upon completion of the required case load as set forth by the ABHRS, will be able to sit for the oral and written boards performed by the ABHRS. Other less intensive options for training exist and these are also outlined in the chapter.
Keywords: fellowship guidelines; candidate selection; core competencies; curriculum; case log requirements